2020
DOI: 10.3389/fmicb.2020.593295
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia trachomatis Plasmid Protein pORF5 Up-Regulates ZFAS1 to Promote Host Cell Survival via MAPK/p38 Pathway

Abstract: Long non-coding RNAs (lncRNAs) have been demonstrated to play essential roles in many diseases. However, few studies have shown that lncRNAs take part in the pathogenesis of Chlamydia trachomatis (C. trachomatis). Here, we used a lncRNA microarray to detect the global lncRNA expression profiles in HeLa cells transfected with pORF5 plasmid protein, an important virulence factor for C. trachomatis. The differentially expressed lncRNAs and mRNAs screened by microarray were selected for validation by quantitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Unfortunately, there is no clinical vaccine for humans (20). Pgp3 is an important virulence protein encoded by the cryptic plasmid (21)(22)(23)(24). Our previous studies confirmed that Pgp3 was a conformationdependent immunodominant antigen, which was an expected vaccine candidate (25).…”
Section: Introductionmentioning
confidence: 84%
“…Unfortunately, there is no clinical vaccine for humans (20). Pgp3 is an important virulence protein encoded by the cryptic plasmid (21)(22)(23)(24). Our previous studies confirmed that Pgp3 was a conformationdependent immunodominant antigen, which was an expected vaccine candidate (25).…”
Section: Introductionmentioning
confidence: 84%
“…It was predicted to regulate MAPK pathways and its silencing led to decrease in Chlamydia plasmid protein pORF5-mediated-apoptosis and Ct virulence (Figure 4C). The study concluded pORF5 crucial role in activation of lncRNA ZFAS1, and ZFAS1 mediated induction of MAPK/p38 pathway to inhibit host cell apoptosis (Wen et al, 2020a).…”
Section: Chlamydia Trachomatismentioning
confidence: 89%
“…Overall, there was acceptable biosafety with respect to CSPE and IL-12 as C. trachomatis vaccine adjuvant candidates. (53)(54)(55)(56), which was essential for the pathogenesis of C. trachomatis. Importantly, Pgp3 was regarded as a promising antigen for subunit vaccine candidates due to existing immunogenicity (17).…”
Section: Biocompatibility Assaysmentioning
confidence: 99%